Work conditions assessment in manufacturing organizations in the colombian caribbean region (2016)
Deficient work conditions have been linked with an epidemic of injury and illness in low and middle-income countries. A group of 22 companies from different sectors was selected in order to carry out a diagnosis related to work conditions in Colombia. To do so, an instrument was designed based on the International Labour Organization (ILO) standards. This information allowed identifying potential problems in work conditions such as work environments, physical load, noise and social welfare. Some low cost measures were discussed as suggestions to improve work conditions. Such measures are expected to generate both an increase in productivity and an enhancement in the employees' attitude.